Analisis Kelayakan Usaha Produksi Tahu Sumedang (Studi Kasus Di Pabrik Tahu XY Kecamatan Conggeang) - Nur Ali Sa'id; Amar Ma'ruf; Delfitriani Delfitriani (JURNAL AGROINDUSTRI HALAL, 2020)
Feasibility analysis of XY tofu production business is a factory that produces traditional food typical of the Sumedang district. This production utilizes the marketing sector and marketing location which is located near the sub-district traditional market. This study aims to analyze the business of tofu Sumedang in the XY tofu factory which includes non-financial aspects (Market aspects, marketing, engineering, management, legal, social and environmental), and financial aspects. Based on non-financial results hat the non-financial aspects affect the operation of the tofu XY production business.  Based on the results of the calculation of financial aspects it is feasible to carry out the NVP value generated for 10 years Rp. 579,177,261 -, with production capacity per month producing tofu 216.000 seed and 6.806 kg tofu dregs per month. The IRR  obtained is 0,41% where the IRR is more than 0%. Net B / C obtained is 2,92, this means, every Rp. 1 spent on running this business will generate net benefits of Rp.2,92. The payback period obtained is 2,63 years. The sensitivity analysis for this project shown an increase in operational / production costs of 10%, an increase in raw materials and additional materials by 20% and a decrease in selling prices by 10% which does not affect this business.Keywords: feasibility business, financial analysis, sensitivity analysis